Refluxing Synthesis and Characterization of UV-Light-Driven Ag-Doped PbMoO4 for Photodegradation of Rhodamine B - Anukorn Phuruangrat (2020)
© 2020, The Minerals, Metals & Materials Society. Silver-doped lead molybdate (Ag-doped PbMoO4) nanoparticles have been successfully synthesized by a reflux method using ethylene glycol as solvent. x-Ray powder diffraction (XRD) analysis, scanning electron microscopy (SEM) with energy-dispersive x-ray spectroscopy (EDS), transmission electron microscopy (TEM), ultraviolet–visible (UV–Vis) spectroscopy, and surface area analysis were used to study the phase content and morphology of the PbMoO4 and Ag-doped PbMoO4 nanostructures. The analytical results showed that all the samples were scheelite-type tetragonal PbMoO4 nanoparticles. The photocatalytic properties of the PbMoO4 and Ag-doped PbMoO4 nanoparticles were investigated through photodegradation reaction of rhodamine B (RhB) under UV light irradiation within 60 min. The 5% Ag-doped PbMoO4 nanoparticles showed the highest photodegradation of 97.33%, being 1.25 times that of the pure PbMoO4 nanoparticles.